Yellow River Basin Management under Pressure: Present State, Restoration and Protection II (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This Special Issue includes twenty original contributions focused on Yellow River basin management under pressure. Considering the unique regional characteristics of the Yellow River in China, the contributions mainly result from research conducted by Chinese universities and research and development institutions. The twenty articles in this Special Issue can be divided into six categories, namely “Characteristics of Yellow River basin”, “Water system and economic society system”, “Water resources allocation and efficient utilization”, “Basin ecological protection and environmental pollution remediation”, “Water–sediment relationship of the Yellow River Basin”, and “Yellow River governance”.